2020
DOI: 10.1021/acsptsci.0c00136
|View full text |Cite
|
Sign up to set email alerts
|

Heme/Hemeoxygenase-1 System Is a Potential Therapeutic Intervention for COVID-19 Patients with Severe Complications

Abstract: Acute respiratory distress syndrome (ARDS) is one of the critical stages of COVID-19, leading to lung injury and hemolysis. Dysfunctional hemoglobin (Hb) suffers low-level oxygenation, overloaded iron, and down-regulation of hemeoxygenase-1 (HO-1), representing potential therapeutic interventions. This Viewpoint outlines the Hb−HO-1 system as a host-cell target, and proposes possible therapies, including iron chelation and CO therapies, against COVID-19 with ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…This results in low-level oxygenation, elevation of free iron and the down regulation of heme oxygenase-1 (HO-1) [ 31 ]. Based on this observation it is speculated that Hb, HO-1 and iron overload are possible targets for the treatment of COVID-19 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This results in low-level oxygenation, elevation of free iron and the down regulation of heme oxygenase-1 (HO-1) [ 31 ]. Based on this observation it is speculated that Hb, HO-1 and iron overload are possible targets for the treatment of COVID-19 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 and heme metabolites have strong antiviral properties (Singh et al, 2020).They also protect against damaging inflammation and coagulopathy (Nath et al, 2020; Dysregulated inflammation and coagulopathy are particularly insidious features of COVID-19 that cause widespread damage to multiple organ systems (Tay et al, 2020). Many have suggested that induction of the HO-1 system by various agents could be of great benefit to patients suffering from COVID-19, (Dattilo, 2020;Fakhouri et al, 2020;Hooper, 2020;Maiti, 2020;Rossi et al, 2020;Singh et al, 2020;Wagener et al, 2020) however this idea is yet to be validated by experimental evidence. Relevant models in which Hemin has been demonstrated as protective include; acute lung injury (X.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of HO-1 centric therapeutics to combat severe COVID-19 has been noted by several groups, yet the role of HO-1 in SARS-CoV-2 infection remains unclear (Dattilo, 2020; Fakhouri et al, 2020; Hooper, 2020; Maiti, 2020; Rossi et al, 2020; Singh et al, 2020; Wagener et al, 2020). Here we present experimental evidence for the antiviral capabilities of the HO-1-inducing drug Hemin in a cell line model of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…This inflammatory response involves several host defense systems such as hemostasis, angiogenesis, and complement. 1 , 2 Comorbidities such as diabetes, hypertension, and obesity, as well as advanced age are associated with higher mortality. 3 …”
Section: Introductionmentioning
confidence: 99%